Perubahan Perilaku Petani Di Desa Cibaregbeg Kecamatan Cibeber Kabupaten Cianjur - jembaran, aria (Journal of Agribusiness, Social and Economic, 2025)
Farmer behaviour is all activities carried out by farmers in carrying out farming activities, the aspects that are seen are 3 indicators, namely, attitude, knowledge, skills, and factors that affect the behaviour of farmers The method used is descriptive to describe the results of the research, the purpose of this study is to find out the role of agricultural extension workers in changing farmers' behaviour The results of the study show that the role of agricultural extension workers is very good and the pattern of farmers' behaviour still needs to be improved, one of which is the use of information search on the internet.